Ajax - Holzner, Steven; Safari eBooks ([S.l.] : Virtual Training Company, 2002)
"Ajax, shorthand for Asynchronous Javascript and XML, is a set of technologies that allows you to create Web applications that don't need to refresh Web pages in the browser. You can operate behind the scenes, connecting to the server, uploading and downloading data, and display the results in the browser using dynamic HTML. Using Ajax gives your Web pages the feel of a desktop application-the whole display will no longer flash when you click a button. VTC Author Steve Holzner helps you get started developing and building your own Ajax capable web pages. A familiarity with JavaScript, XML, PHP is recommended for this course. To begin learning, simply click the links."--Resource description page.
Title and publication information from resource description page (viewed Aug., 11, 2011).
Keywords: Ajax (Web site development technology); Web sites -- Design; Web site development; Electronic books